Pengolahan sampah organik di Kota Gunungsitoli - Nicolas Yudistira Harefa; Kancitra Pharmawati (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2022)
Waste is unwanted residual material after a process is complete. Garbage that is not managed properly will lead to waste problems. Gunungsitoli City is one of the areas experiencing solid waste problems. Increasing population growth results in more and more waste generation. Garbage services in Gunungsitoli City are still 49.1% so that there are still 50.9% of people who have not been served. The aim of this research was to determine the processing of organic waste to reduce the waste that goes to the landfill. The research method used was descriptive qualitative analysis by analyzing waste management at the study site and providing recommendations for other waste management. The average amount of waste generated per day in Gunungsitoli City in 2020 is 133,828 m3/years. The most waste generated in Gunungsitoli City is organic waste by 71% and inorganic waste by 29%. Waste processing in Gunungsitoli City is carried out at the TPA by composting. Another alternative for processing organic waste that can be done is processing organic waste using maggot. In addition, organic waste processing also needs to be done with a recycling process.